ABSURDITAS DALAM DRAMA LES MOUCHES KARYA JEAN-PAUL SARTRE - Birul Sinari Adi (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
This study is an attempt to assess absurdity in Les Mouches as a concept of pessimistic humanism. Regarding the issues expressed through the work may be understood on the humanism perspective, then, the aims to be achieved through this research is the understanding of the humanity issues, which have a great extent of possibilities expressed through the literary work. The drama play of Les Mouches is actually the manifestation of the problems of the human life, which deal with many possibilities as well. As a text, Les Mouches is a structure that arranges its constituent elements to create meaning. And within its function, Les Mouches, as a social and cultural phenomenon, is a communication act. This means that a literary work is a sign, and through this sign the literary work may be the expression thrusting concrete and fictitious experiences of the entire human life.